Detection of miRNA-15a, miRNA-29b, miRNA-34a and miRNA-223 in Cow, Sheep, Goat, Buffalo, and Donkey Milk and Investigation of Their Relationship with Milk Composition - çelik, ahmet; VURAL, AYDIN; YILDIRIM, İBRAHİM HALİL (Journal of the Hellenic Veterinary Medical Society, 2025)
The objective of this study was to ascertain the expression levels of miRNA-15a, miRNA-29b, miRNA-34a, and miRNA-223 in milk from cows, buffaloes, sheep, goats, and donkeys and to examine their relationship with milk composition. The miRNA expression levels were quantified by RT-qPCR, and their correlation with the physicochemical data of the milk was examined. The expression of miRNAs was observed in all milk samples and there was a correlation between miRNA expression and milk fat, protein, dry matter and pH. A positive correlation was observed between fat and miRNA-34a in cows’milk, a positive correlation between fat and miRNA-29b in donkey milk (P<0.05), and a negative and significant correlation between fat and miRNA-29b in sheep milk (P<0.05). A positive and significant correlation was identified between dry matter and miRNA-34a in sheep milk (P<0.05), whereas a negative and significant correlation was observed between dry matter and miRNA-223 in goat milk (P<0.05). Additionally, a negative and significant correlation was found between dry matter and miRNA-29b in sheeps’milk (P<0.05). A positive and significant relation ship was identified between miRNA-34a expression and pH in sheep milk (P<0.05). It can be concluded that miRNAs play an important role in milk composition, hygiene, health and technology. Further studies are recommended to gain a deeper understanding of these aspects.